2023
DOI: 10.26803/ijlter.22.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Divulging the Lived Experiences of Public School Teachers in the U.S.A. during COVID-19 Pandemic: Phenomenological Analysis

Jaypee R Lopres,
Glendale Y Niadas,
Geraldine P Minez
et al.

Abstract: This research examined the lived experiences of public school teachers in the United States during the COVID-19 pandemic. A qualitative design was performed using interpretative phenomenological analysis. Twenty public school teachers in the United States formed the sample, with the inclusion criterion being a minimum of three years’ teaching experience, including the pandemic. To meet the safety measure protocols set by the U.S. government, the data gathering was conducted online using Microsoft Forms. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the United States, Lopres et al (2023) also discovered that because of the erratic internet connection, teachers have found it challenging to involve students in group projects, interactive lessons, and class discussions. Some students have even claimed that they are completely unable to participate in online classes.…”
Section: Emergent Theme 3: Accuracy Level Of Assessment Resultsmentioning
confidence: 99%
“…In the United States, Lopres et al (2023) also discovered that because of the erratic internet connection, teachers have found it challenging to involve students in group projects, interactive lessons, and class discussions. Some students have even claimed that they are completely unable to participate in online classes.…”
Section: Emergent Theme 3: Accuracy Level Of Assessment Resultsmentioning
confidence: 99%
“…Submission of teaching materials using these two media is very effective and can save costs. The use of electronic technology as a learning medium was needed to respond to the needs of interactive learning during the COVID-19 pandemic [20]. Then during the post-pandemic COVID-19 as recovery period, the use of electronic communication is still needed as part of hybrid learning tools in Indonesia which in this study are called audio-visual.…”
Section: Audiovisual Mediamentioning
confidence: 99%
“…Several studies (Bartlett et al, 2020;Gassman-Pines et al, 2020;UNICEF, 2020) point to great harm to emotional wellbeing. Reports such as the OECD (2021) indicate impairment of academic performance; Lopres et al (2023) found that student motivation and engagement in online learning were significantly affected.…”
Section: Literatures Reviewmentioning
confidence: 99%